Radiation therapy in clinically node positive HER2 positive breast cancer after primary systemic therapy and breast conserving surgery: pooled analysis of TRYPHAENA and NeoSphere trials - Mohamad El-Jammal; Omran Saifi; Jose Bazan; Youssef H. Zeidan (BMC Cancer)
Abstract Background The benefit of regional nodal irradiation (RNI) following modern primary systemic therapy (PST) in HER2-positive breast cancer (HER2 + BC) remains under investigation. The current study evaluates RNI practice patterns and outcomes based on the pathological response to PST in clinically node-positive (cN+) HER2 + BC. Methods TRYPHAENA and NeoSphere are two randomized phase II trials that investigated PST for HER2 + BC. The current study is a pooled analysis of both trials, focusing on cN + patients treated with HER2-targeted PST followed by breast-conserving surgery. The primary goal is to describe patterns of RNI practicein this population and its impact on breast cancer recurrence-free survival (BCRFS) and loco-regional recurrence-free survival (LRRFS). Results Our analysis included a total of 90 patients with cN + disease. Complete nodal pathological response was achieved in 53 patients (58.9%). Patients with ypN0 had a 5-year LRRFS of 95.83% whereas patients with ypN + had 5-year LRRFS of 87.43% (p = 0.105). RNI was used in 16 ypN0 (48.5%) patients and 17 ypN+ (51.5%) patients. Patients treated with RNI had 5-year LRRFS of 93.4% as compared to 92.5% in the no RNI group (p = 0.868). Distant metastasis was detected in 5 patients (5%) with the most common sites being: liver, lung, bone, and CNS. Locoregional recurrence was significantly associated with distant failure (p = 0.002). Conclusions cN + HER2 + BC patients who achieve ypN0 after PST have excellent locoregional control. In contrast, patients with ypN + tend to have lower locoregional control. The utility of RNI in HER2 + BC warrants further investigation.